Cognitive flexibility supports preschoolers' detection of communicative ambiguity. Issue 1 (February 2014) - Gillis, Randall; Nilsen, Elizabeth S.
To become successful communicators, children must be sensitive to the clarity/ambiguity of language. Significant gains in children's ability to detect communicative ambiguity occur during the early school-age years. However, little is known about the cognitive abilities that support this development. Relations between cognitive flexibility and ambiguity detection were assessed in preschool- (4- to 5-years-old, n = 40) and school-age (6- to 7-years-old, n = 36) children. Children rated the quality of clues (unambiguous/ambiguous) to the location of hidden stimuli provided by a videotaped speaker. Cognitive flexibility was assessed through a task requiring children to sequentially sort toys. Both age groups rated ambiguous clues as less helpful than unambiguous clues; however, school-age children were better able to detect ambiguity. Cognitive flexibility was related to preschool (but not school-age) children's communicative ambiguity detection, when controlling for age and receptive language. Results suggest that cognitive flexibility may be particularly important for the initial development of ambiguity detection.